Prevalence of Linea Alba Buccalis in Bangladeshi Population - Md Anisuzzaman, Mostafa; Khan, Mohammad Tariqul Islam; Hasan, Sajid; Adnan, Nubad; Afrin, Alia (Update Dental College Journal, 2019)
Aim: The aim of this study is to determine the prevalence of linea alba buccalis in Bangladeshi population. Objective: To study the prevalence of frictional keratosis encompassed by the particular age groups with and without parafunctional habits. Background: Linea alba buccalis is a thickened whitish line on the buccal mucosa at the horizontal of the occlusal plane extending from the corners of the mouth to the posterior teeth. It is usually correlated with the frictional activity of the teeth and may be emphasized by cheek biting or parafunction. The appearance is caused by a keratosis of the epithelial tissue, which cannot be rubbed off. It is asymptomatic and is frequently present bilaterally. The condition does not require treatment. Logic: Linea alba buccalis being common finding, it may also found in individuals who chew tobacco, a thorough analysis of the prevalence along with the various contributing factors would assist in prompt treatment and prevent further complications. Update Dent. Coll. j: 2019; 9 (2): 17-19